Rethinking rainfall: exploring opportunities for sustainable stormwater management practices in Turkey Creek Basin and downtown Kansas City - Ptomey, Patrick (Kansas State University, 2013)
Kansas City’s outdated sewer system is presently incapable of capturing and treating the increased runoff volumes in Turkey Creek Basin during rainstorm events. As a result, 2.66 billion gallons of untreated sewer system overflow is released annually into the Kansas River and nearby properties. In 2002, the Environmental Protection Agency issued a civil action requiring the City of Kansas City, Missouri, to take appropriate and necessary actions needed to prevent or minimize the discharge of untreated sewage. In response, the City of Kansas City adopted a comprehensive Overflow Control Plan intended to reduce sewer system overflow volumes in Turkey Creek Basin by 85% at a cost of approximately $244 million. Initially, the City of Kansas City seriously considered implementing stormwater best management practices (BMPs) in place of sewer system improvements. Stormwater BMPs infiltrate, filter, store, and evaporate stormwater runoff close to its source, preventing stormwater runoff from reaching the sewer system. Subsequently, many BMPs were eliminated from the Overflow Control Plan and replaced with conventional sewer system technologies because of performance concerns. However, the Overflow Control Plan acknowledged that BMPs located on private property would indirectly benefit Kansas City’s stormwater management strategy. Using geographic information system (GIS) analysis, suitability maps were generated for twelve different BMPs to determine suitable locations in Turkey Creek Basin for reducing stormwater runoff. Analysis concluded that the most effective strategy for sustainable stormwater management would be to locate BMPs at higher elevations within the watershed to prevent upland runoff from flooding sewer system pipes at lower elevations. Areas having the highest suitability are located primarily on residential land, implying that Kansas City could benefit most from encouraging its residents to equip their properties with site-appropriate BMPs. This can be achieved through educational initiatives, policy adoption, and homeowner incentives. Therefore, policies and incentives targeting Kansas City’s residents should be implemented to reduce sewer overflow volumes and prevent future costly improvements to Kansas City’s sewer system.
Keywords: Best management practices; Kansas City; Combined sewer overflow; Landscape Architecture (0390)